PEDAGANG LEPAT BUGI DI JALAN LINTAS PEKANBARU-BANGKINANG DESA DANAU BINGKUANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Ekky Andre Pratama; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine the socio-economic background of Lepat Bugi trader and the strategy of trader in the confront of competition among fellow Lepat Bugi traders in the village of Danau Bingkuang. Research conducted using qualitative approach method. Informants are chose using a purposive sampling and techniques in data collection by using the techniques of observation, interview, and documentation. Subjects in this study are Lepat Bugi trader that exist in the village of Danau Bingkuang. Informants selected as many as 5 people based on certain criteria. The results of this study indicate that the Lepat Bugi traders has a moderate socio-economic background, this can be seen in terms of income that can meet the needs of his family and life, the ownership of household facilities, and the level of education is low. The form of competition that occurs among fellow Lepat Bugi traders that is healthy and unhealthy competition. The happening competition is how the traders can attract as many buyers and make a profit. The strategy used by Lepat Bugi traders to confront the competition is active strategy, passive strategy, and network strategy. This strategy is very necessary for traders to survive in running their business so that it can be passed on to the next generations.Keywords: socio-economic background, competition, and strategy